GENETICALLY DEFINED AUTOINFLAMMATORY DISEASES - DE JESUS, ADRIANA ALMEIDA (Oral Dis, 2016)
Autoinflammatory diseases are hyperinflammatory, immune-dysregulatory conditions that typically present in early childhood with fever and rashes and disease-specific patterns of organ inflammation. This review provides a historic background of autoinflammatory disease research, an overview of the currently genetically defined autoinflammatory diseases, and insights into treatment strategies derived from understanding of the disease pathogenesis. The integrative assessment of autoinflammatory conditions led to the identification of innate pro-inflammatory cytokine “amplification loops” as the cause of the systemic and organ-specific disease manifestations, which initially centered around increased IL-1 production and signaling. More recently additional innate proinflammatory cytokine amplification loops resulting in increased Type I IFN, IL-17, IL-18 or IL-36 signaling or production have led to the successful use of targeted therapies in some of these conditions. Clinical findings such as fever patterns, type of skin lesions, genetic mutation testing, and the prevalent cytokine abnormalities can be used to group autoinflammatory diseases.